A Pilot Study of Protein Microarray for Simultaneous Analysis of 274 Cytokines Between Abdominal Aortic Aneurysm and Normal Aorta. (October 2019) - Yuwen, Li; Ciqiu, Yang; Yi, Shi; Ruilei, Liu; Yuanhui, Lai; Bo, Lin; Songqi, Li; Weiming, Lv; Jie, Li
Cytokines play an important role in the pathogenesis of abdominal aortic aneurysm (AAA). We evaluated the cytokine expression profile of large AAA walls using a 274-cytokine protein array. We hypothesized that AAAs are characterized by an inflammatory, chemotactic cytokine profile. We investigated the cytokine expression profile of 12 patients with AAA and 6 nonaneurysmal controls using an antibody-based protein array. The array generated antibodies against homogenized human aortic tissues to validate the cytokines differentially expressed in AAAs and normal aortas. Data were quantified using fluorescent signal intensities and statistically analyzed by the t test. Fifty-nine cytokines were differentially expressed between the AAA and control samples. Of the 35 selected cytokines that had relative expression >1000, 29 were significantly higher and 6 were lower in AAA samples than in controls. They respectively belonged to CC chemokines, CXC chemokines, pro-inflammatory cytokines, growth factors, proteolytic proteins and inhibitors, and cell adhesion cytokines. Our results show that distinct cytokines are involved in AAAs and suggest that the pathways involving these cytokines may be associated with the pathogenesis and development of AAAs. These findings, if confirmed by larger studies, may suggest treatment targets.